MEKANISME CORPORATE GOVERNANCE: DAMPAKNYA PADA PEMBENTUKAN INTELLECTUAL CAPITAL PERUSAHAAN INDEKS LQ45 (Faletehan Jurnal Ekonomi dan Bisnis, 2022)
This study aims to examine the effect of corporate governance which is proxied by the institutional and managerial share ownership structure and the composition of independent commissioners on intellectual capital. The object of research was carried out at companies listed on the LQ45 index with a total sample of 19 companies. Data analysis using multiple linear regression method processed by the SPSS program. Based on the results of statistical tests, the results obtained 1) Institutional ownership has a positive and significant effect on intellectual capital as evidenced by the regression coefficient value of 0.564 and significance of 0.025. 2) Managerial ownership has no effect on intellectual capital as evidenced by the regression coefficient value of 0.061 and significance of 0.294. 3) Independent commissioners have a positive and significant effect on intellectual capital as evidenced by the regression coefficient value of 0.806 and significance of 0.047.